THE IMPROVEMENT OF SIMPLE EXPLANATION AND INFERENCETION SKILLS WITH PROBLEM SOLVING - Fransiska Olivia Dewanti; Chansyanah Diawati; Noor Fadiawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The learning process is strongly influenced by the ability and accuracy of teachers in selecting and applying the learning model. The model can be applied to improve of  simple explanation and inferencetion skill is a model of problem solving. The purpose of this study was to describe the model of problem solving that are effective in improving simple explanation and inferencetion skills on the material electrolyte and non-electrolyte solution. This research use a quasi-experimental methods with Non Equivalent (Pretest and Posttest) Control Group Design. The sampling technique used purposive sampling technique. The samples in this study were high school students Bandar Lampung Fransiskus X4 and X5 class even semester 2012-2013 School Year. Effectiveness of the learning model of problem solving is measured based on a significant increase in gain and t-test. The results showed the average value of n-Gain a simple explanation skills for the control and experimental classes 0.47 and 0.75, while the average n-Gain inferencetion skills to control and experimental classes 0.54 and 0.66. This suggests that learning is effective in improving of simple explanation and inferencetion skills with problem solving.Keywords: Problem Solving, a simple explanation skills, inference skills